Activity Level and Severity of Dysplasia Predict Age at Bernese Periacetabular Osteotomy for Symptomatic Hip Dysplasia. (20th April 2016) - Matheney, Travis; Zaltz, Ira; Kim, Young-Jo; Schoenecker, Perry; Millis, Michael; Podeszwa, David; Zurakowski, David; Beaulé, Paul; Clohisy, John
Abstract : Background: The age when patients present for treatment of symptomatic developmental dysplasia of the hip with periacetabular osteotomy (PAO) varies widely. Modifiable factors influencing age at surgery include preexisting activity level and body mass index (BMI). The severity of the hip dysplasia has also been implicated as a factor influencing the age at arthritis onset. The purpose of this study was to determine whether activity level, BMI, and severity of dysplasia are independent predictors of age of presentation for PAO. Methods: A retrospective, institutional review board-approved review of prospectively collected data from a multicenter study group identified 708 PAOs performed for developmental dysplasia of the hip. Demographic factors that were considered in the analysis included age at surgery, BMI, history of hip disorder or treatment, and duration of symptoms. The severity of the developmental dysplasia of the hip was assessed by radiographic measurement of the lateral and anterior center-edge angles and acetabular inclination. Activity level was assessed with the University of California, Los Angeles (UCLA) activity score. Spearman correlations and t tests were used for univariable analysis. Multivariable regression analysis using generalized estimating equations was applied to determine independent predictors of age at PAO. Results: Univariable analysis indicated that age at presentation for treatment of PAO correlated with the lateral and anterior center-edge angles (p < 0.001), UCLA score (p < 0.001), and BMI (p = 0.04). Since the lateral and anterior center-edge angles were similarly correlated (Spearman rho = 0.61, p < 0.001), the lateral center-edge angle alone was used to classify the severity of the developmental dysplasia of the hip. Multivariable linear regression confirmed that a high UCLA score and severe hip dysplasia were independent predictors of age at PAO (p < 0.001). Conclusions: A high activity level and severe dysplasia lead to the development of symptoms and presentation for PAO at significantly younger ages. The combination of these two factors has an even greater effect on decreasing the age at presentation for hip-preserving surgery. An increased BMI was not independently associated with a younger age at surgery. Modifying activity level may be beneficial in terms of delaying the onset of symptoms from developmental dysplasia of the hip. Level of Evidence: PrognosticLevel IV . See Instructions for Authors for a complete description of levels of evidence.